PENGARUH KEJELASAN SASARAN ANGGARAN DAN EVALUASI ANGGARAN TERHADAP PENGAWASAN ANGGARAN (STUDI EMPIRIS PADA KABUPATEN KAMPAR) - Aras Aira (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2012)
The research soughtly to test the effect of budget quality consisting of the budget target clarity, the budget evaluation on the budget supervision effectivity.. The population of the research was the members of parliament serving for the period of 2009-2014. The data were the collected using a quaestionnaire to 43 members of parliament, however only 34 quaestionnaires were returned.The result revealed that the budget target clarity, the budget evaluation significantly effected the supervision effectivity.